Artificial Intelligence Adoption in Smaller Audit Practices - Karim, Mohd Syazwan; Mohd Pauzi, Nur Farahah; Shamsudin, Adriana; Mamat, Siti Nurulhuda; Abdul Fatah, Muhammad Mukhlis; Ahmad, Khairiah; Roslan, Nurfarahin (Information Management and Business Review, 2025)
The emergence of new technologies, such as Artificial Intelligence (AI), is anticipated to profoundly impact the accounting and auditing sectors. AI is essential for automating repetitive tasks and enhancing audit judgment. This study seeks to investigate the adoption of AI in small audit firms in Malaysia. A qualitative research design was employed, involving semi-structured interviews with nine audit supervisors from small audit firms in Kuala Lumpur, Negeri Sembilan, Pahang, and Melaka. The discussion focuses on two elements: (1) Perceived Usefulness (PU) – emphasizing how AI enhances audit efficiency and accuracy, and (2) Perceived Ease of Use (PEU) – highlighting the ease of adoption and integration of AI tools into existing audit workflows. The findings reveal that AI is perceived as a valuable tool in small audit firms, improving audit quality and workflow by significantly accelerating the audit process. However, human expertise is still required for certain complex tasks and decision-making. Hence, it is crucial to communicate the AI’s capabilities and constraints to prevent users from experiencing undue disappointment. The findings of this study aim to assist regulators and standard-setters in developing guidelines, principles, and frameworks for AI adoption among audit firms in Malaysia.